Selective binding and release of aspirin by an encapsulating receptor - Nguyen, Thanh Vinh; Yoshida, H.; Sherburn, M. (The Royal Society of Chemistry, 2010)
The selective binding of aspirin deep inside superbowl synthetic hosts is reported. Evidence for a two-point binding mode of the drug by the host is presented. Both the strength of aspirin binding and the rate of its release are manipulated by altering the substituents about the host’s aperture